Investigation of a theoretical model for the rotational shot put technique - Kato, T.; Maeda, K.; Mizushima, J.; Maeda, A. (Journal of Applied Biomechanics, 2024)
The biomechanics of the rotational shot put technique have been demonstrated. However, the causal relationships among kinematics and kinetics for achieving higher release velocity remain poorly understood. This study investigated these causal relationships among biomechanical variables for achieving a higher release velocity in the rotational shot put technique. The study included 22 male shot putters whose 3-dimensional motion was captured during official competitions. Key kinematic and kinetic variables throughout the shot put motion were calculated, as suggested by previous studies. Path analysis was used to explore a hierarchical model that postulates both direct and indirect effects among variables. The findings revealed that the impulse of the shot, system angular momentum, and system linear momentum were critical kinetic variables contributing directly to release velocity. Additionally, 8 kinematic variables significantly affected the impulse of the shot, including shoulder rotation, shot path length, and trunk tilt, while movements such as swings and extensions of the lower extremities were related to system momentum. This model not only provides a detailed understanding of the mechanics involved in the rotational technique but also informs technical coaching strategies in the shot put.